EVALUASI PRESTASI KERJA PENANAMAN PADA PROYEK REHABILITASI DAERAH ALIRAN SUNGAI BERDASARKAN TIPE TUTUPAN LAHAN - Ardima Tidore; Hengki D. Walangitan; Martina A. Langi (COCOS, 2018)
Abstract Land cover type is a factor that needs to be taken into account in an effort to rehabilitate a watershed as it can affect planting activities, resulting in varying use of working time.Â  Nevertheless, technical instructions applied to reforestation are still general. Therefore there is a need for a standard working time in reforestation (planting) as a guideline in determining policies in planting activities. This research was conducted in Bantik Village, Bolaang Timur District, Bolaang Mongondow Regency during one month. to analyze the work performance of planting on several types of land cover. The study used repetitive timing for data collection method which is then analyzed and furtherly tested with ANOVA. The results showed that land cover has a significant effect on work performance, the work performance of planting on young shrub land cover has the highest achievement of 16 seeds per hour followed by an old shrub of 15 seeds per hour and bush of 12 seeds per hour. Keywords: Work performance, plantation, land cover